Doubles tennis tactics - International Tennis Federation (Champaign, Ill. Human Kinetics, 2001)
Doubles Tennis Tactics Video covers the most effective patterns for team strategy, serving, receiving, poaching, movement, and positioning. Learn these patterns, and you will dramatically improve your doubles play.
With 1 converted disc.
VHS format.
In English
Keywords: Tennis -- Doubles